Expression and crystallization of a bacterial glycoside hydrolase family 116 β‐glucosidase from Thermoanaerobacterium xylanolyticum. Issue 1 (1st January 2015) - Sansenya, Sompong; Mutoh, Risa; Charoenwattanasatien, Ratana; Kurisu, Genji; Ketudat Cairns, James R.
<x xml:space="preserve">Abstract</x> The Thermoanaerobacterium xylanolyticum gene product TxGH116, a glycoside hydrolase family 116 protein of 806 amino‐acid residues sharing 37% amino‐acid sequence identity over 783 residues with human glucosylceramidase 2 (GBA2), was expressed in Escherichia coli. Purification by heating, immobilized metal‐affinity and size‐exclusion chromatography produced >90% pure TxGH116 protein with an apparent molecular mass of 90 kDa on SDS–PAGE. The purified TxGH116 enzyme hydrolyzed the p‐nitrophenyl (pNP) glycosides pNP‐β‐D‐glucoside, pNP‐β‐D‐galactoside and pNP‐N‐acetyl‐β‐D‐glucopyranoside, as well as cellobiose and cellotriose. The TxGH116 protein was crystallized using a precipitant consisting of 0.6 M sodium citrate tribasic, 0.1 M Tris–HCl pH 7.0 by vapour diffusion with micro‐seeding to form crystals with maximum dimensions of 120 × 25 × 5 µm. The TxGH116 crystals diffracted X‐rays to 3.15 Å resolution and belonged to the monoclinic space group P21. Structure solution will allow a structural explanation of the effects of human GBA2 mutations.